Refining the Ethics of Leadership-as-Practice: A Counter-Case Analysis - Joseph A. Raelin (Business and Professional Ethics Journal, 2022)
The field of leadership-as-practice (L-A-P) is beginning to mature as a theory of leadership in direct opposition to standard leadership, which views the individual as the mainstay of leadership experience. Nor does it focus on the dyadic relationship between leaders and followers, which historically has been the starting point for any discussion of leadership. Rather, it is concerned with how leadership emerges and unfolds through day-to-day experience. In this ongoing and evolving activity, questions of ethics arise which challenge what appears to be a flat ontology circumscribing its ethical applications. Using a case analysis, which according to the author takes significant liberties with some of the fundamental ethical principles and practices of L-A-P, this essay seeks to refine and delineate what constitutes business ethics from a leadership-as-practice perspective.
Keywords: N35; D63; M51; M54; 330; business ethics; practice turn; leadership-as-practice; dialogue; ontology; epistemology